Bridging Pedagogy and Technology: Stress Triggers and Strategies Among English Language Teachers - Indahyanti, Rizka; Rahman, Ali Wira; Andy Hamzah Fansury (Eduvelop: Journal of English Education and Development, 2025)
This study explores the stress experienced by English language teachers in educational settings, with a focus on identifying the key stressors and the coping strategies they employ. A qualitative approach was used, involving semi-structured interviews and classroom observations with 32 participants selected through purposive sampling. The data revealed that English language teachers face a range of stress-inducing factors, including inadequate student competence and discipline, insufficient learning support facilities, regulatory pressures, low salaries, increased workloads, and limited teacher competence. These stressors negatively impact their performance, motivation, and overall well-being. In response to these challenges, teachers adopt various coping strategies to manage stress effectively. These include efforts to improve their pedagogical knowledge and professional skills, integrating technology into the teaching and learning process, applying better time management practices, and fostering a more positive and supportive classroom environment. Additionally, teachers demonstrated resilience by attempting to exert control over stress-inducing factors within their professional context. The study underscores the complex and multifaceted nature of teacher stress, emphasizing the importance of institutional support in addressing these issues. It advocates for the development and implementation of targeted support programs aimed at improving the mental health and well-being of EFL teachers. By understanding the sources of stress and how teachers cope with them, stakeholders in the education sector can better design interventions to create a more supportive and sustainable teaching environment.